Hyporheic Source and Sink of Nitrous Oxide. Issue 7 (26th July 2018) - Reeder, W. Jeffery; Quick, Annika M.; Farrell, Tiffany B.; Benner, Shawn G.; Feris, Kevin P.; Marzadri, Alessandra; Tonina, Daniele
Abstract: Nitrous oxide (N2 O) is a potent greenhouse gas with an estimated 10% of anthropogenic N2 O coming from the hyporheic zone of streams and rivers. However, difficulty in making accurate fine‐scale field measurements has prevented detailed understanding of the processes of N2 O production and emission at the bedform and flowline scales. Using large‐scale, replicated flume experiments that employed high‐density chemical concentration measurements, we have been able to refine the current conceptualization of N2 O production, consumption, and emission from the hyporheic zone. We present a predictive model based on a Damköhler‐type transformation (τ̃) in which the hyporheic residence times (τ) along the flowlines are multiplied by the dissolved oxygen consumption rate constants for those flowlines. This model can identify which bedforms have the potential to produce and emit N2 O, as well as the portion and location from which those emissions may occur. Our results indicate that flowlines with τ̃up ( τ̃ as the flowline returns to the surface flow) values between 0.54 and 4.4 are likely to produce and emit N2 O. Flowlines with τ̃up values of less than 0.54 will have the same N2 O as the surface water and those with values greater than 4.4 will likely sink N2 O (reference conditions: 17C, surface dissolved oxygen 8.5 mg/L). N2 O production peaks approximately at τ̃  = 1.8. A cumulative density function of τ̃up values for all flowlines in a bedform (or multiple bedforms) can be used to estimate the portion of flowlines, and in turn the portion of the streambed, with the potential to emit N2 O. Plain Language Summary: Nitrous oxide (N2 O) is a potent greenhouse gas that has been increasing its atmospheric warming impact. Globally, an estimated 10% of the N2 O that is released to the atmosphere comes from rivers and streams. These emissions are strongly correlated to nitrogen compounds from industrial and agricultural runoff. However, not all streams that are impacted emit N2 O. Clearly, streams have some control over the chemical activity that occurs within their banks. However, the large‐scale studies that have provided the global estimates of N2 O emissions have not been able to pinpoint the mechanisms that control emissions or where within a steam emissions originate. Most of the chemical activity in rivers and streams occurs within the sediments directly adjacent to the stream flow. This volume of saturated sediments is called the hyporheic zone. Surface water flows into the hyporheic sediments carrying with it dissolved chemicals and eventually returns to the surface flow carrying reacted chemical products, potentially among these is N2 O. We demonstrate that this flow exerts control over the biological processes that are the primary source of N2 O emissions from rivers and streams and present a mathematical model that predicts which flowlines have the correct properties to produce and emit N2 O. Key Points: Only a portion of the flowlines through the hyporheic are likely to emit N2 O, while others will sink N2 O to below instream concentrations A framework for identifying the source location of N2 O emissions at the flowline level is presented Peak N2 O production occurs in portions of a bedform with relatively high hyporheic velocities and intermediate residence times